Gambaran Derajat Grit Pada Siswa-Atlet Di Sma Negeri Olahraga Jawa Timur - Jumi Oktaviasari; Widyastuti (Research Parks Publishing LLC, 2021)
Student-athletes have dual demand namely academics and sports achievements. Grit is able to explain student-athletes perseverance and consistency for their achievements. This study aimed to describe the level of Grit in student-athletes at SMA Negeri Olahraga Jawa Timur. This study is a descriptive quantitative research. Respondents in this study were 214 student-athletes in academic year 2020/2021 and the sample were 135 studentsathletes with the sampling technique proportionate stratified random sampling. Measuring instrument used in this study was a Grit scale consists of 12 items (α = 0,671). The results showed moderate level grit was 72,6% and high level grit was 27,4% it can be concluded that student athletes Grit level tends to be high